ANALISIS AKUNTABILITAS INFORMASI PUBLIK PADA PORTAL INFORMASI DAN DOKUMENTASI MILIK TENTARA NASIONAL INDONESIA - Surati; Saefudin Zuhri (PRESIDENSI: Jurnal Politik dan Pemerintahan, 2025)
This research aims to analyze Public Information Accountability Study on the Information and Documentation Management Officer Portal of the Indonesian National Army and identify factors that influence the accountability of public information on the information and documentation management official portal of the Indonesian National Army. This research uses a qualitative approach with interview techniques, observation and focus group discussions to gain deeper understanding. The findings of this research indicate that the TNI PPID Website encourages open information towards a transparent process in the TNI military world. In principle, transparency is part of the government's efforts to foster public trust in the government while involving the public in carrying out the controlling function of all efforts or endeavors carried out by the government in order to improve the welfare of the community. The e-government model framework was also initiated by the United Nations (UN) in 2012. This model was developed based on the ranking of UN member countries. The stages are defined as Emerging Presence, Enhanced Presence, Transactional Presence, and Connection Service.